Prototype design of crowdfunding-based student tuition payment E-Wallet management application (startup) at STMIK Bandung Bali - Andisana, I Putu Gd Sukenada; Smrti, Ni Nyoman Emang; Atho’illah, Ibnu (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2025)
This research designed and developed a prototype e-wallet management application for crowdfunding-based tuition fee payment at STMIK Bandung Bali, addressing higher education cost challenges. Using Agile methodology, the development covered requirements analysis, UI/database design, payment gateway integration, and testing. Core functionalities include student data, academic history, billing, e-wallet balance, donor contributions, and campus operator disbursements. Functional testing showed 100% success across all 9 black-box test scenarios, confirming successful crowdfunding system implementation. However, load and stress tests on shared hosting (0.5 CPU, 256 MB RAM) revealed performance limitations. Response times increased sharply from 2.2 seconds (100 requests) to 14.6 seconds (200 requests), with over 95% system failure beyond 400 concurrent requests, indicating hosting resource constraints. Empirical user evaluations (10 students, 5 donors, 2 operators) confirmed high system effectiveness and usability, yielding average scores of 4.2 for effectiveness and 4.0 for usability (on a 5-point Likert scale). Security measures include private key API integration, AES password encryption, and restricted sensitive data access. This research's success lies in its specific technical solution for institutional tuition crowdfunding, integrating directly with STMIK Bandung Bali's financial management, differentiating it from general platforms.